Engineering a ternary one-dimensional Fe2P@SnP0.94@MoS2 mesostructure through magnetic-field-induced self-assembly as a high-performance lithium-ion battery anode. Issue 33 (4th April 2022) - Liu, Jinyun; Zhou, Ting; Han, Tianli; Zhu, Liying; Wang, Yan; Hu, Yunfei; Chen, Zhonghua
Abstract : A novel ternary one-dimensional mesostructure composed of MoS2 nanosheets grown in situ on SnP0.94 nanotubes embedded with Fe2 P nanospheres is developed through magnetic-field-induced self-assembly, and displays a long cycle life for lithium storage. Abstract : Engineering energy-storage materials possessing high-speed electronic and ionic transport properties for secondary batteries is significant. Here, we develop a ternary one-dimensional mesostructured anode composed of MoS2 nanosheets grown in situ on SnP0.94 nanotubes infilled with Fe2 P nanospheres, which is prepared by magnetic-field-induced self-assembly. The mesostructure provides fast transport pathways for electrons, as verified through a galvanostatic intermittent titration technique; and the voids effectively alleviate the volume change, enabling long-term cycling stability. The Fe2 P@SnP0.94 @MoS2 anode displays a high capacity of 797.5 mA h g −1 after cycling 800 times at 2 A g −1, a coulombic efficiency of 99.4%, and stable rate-performance after three rounds of cycling. Furthermore, the anode shows high capacities at different temperatures, indicating that the composite presented here has a promising potential for use in real conditions.